A strategy to enhance management of free basic water via communal taps in South Africa. (June 2020) - Scheihing, Konstantin W.; Tanner, Jane; Weaver, Matthew; Schöniger, Matthias
Abstract: About 7.5 million South Africans access gratuitous drinking water via communal taps provided by municipalities under a free basic water policy. Supplying running water for free to low-income communities is essential but can result in water wastage due to a potential indifference of non-paying end-consumers. The consequence is a loss of municipal water and financial resources. We outline a new strategy that rewards low-income communities for reducing water wastage. The incentive strategy promotes water conservation and community development and decreases recurring water-related public expenses. The concept is funded by a percentage of municipal cost savings yielded from the respective water conservation. Graphical abstract: Image 1 Highlights: Novel strategy to reduce wastage of freely supplied basic water in South Africa. The concept introduces a win-win situation for involved stakeholders. The strategy is of relevance for Sustainable Development Goal 6. Strategy is exemplified by data of a South African municipal utility.